Erythema Infectiosum: A Narrative Review - Leung, Alexander K. C.; Lam, Joseph M.; Barankin, Benjamin; Leong, Kin F.; Hon, Kam Lun (Current Pediatric Reviews, 2024)
Background: Erythema infectiosum occurs worldwide. School-aged children are most often affected. Since the diagnosis is mainly clinical, physicians should be well-versed in the clinical manifestations of erythema infectiosum to avoid misdiagnosis, unnecessary investigations, and mismanagement of the disease. Objectives: The purpose of this article is to familiarize physicians with the wide spectrum of clinical manifestations and complications of erythema infectiosum associated with parvovirus B19 infection. Methods: A search was conducted in July 2022 in PubMed Clinical Queries using the key terms
Keywords: “slapped cheek” appearance